Investigating the Effect of Operation Mode and Manifestation on Physicalizations of Dynamic Processes - Pahr, Daniel; Ehlers, Henry; Wu, Hsiang‐Yun; Waldner, Manuela; Raidou, RenataG (Computer graphics forum, 2024)
We conducted a study to systematically investigate the communication of complex dynamic processes along a two‐dimensional design space, where the axes represent a representation's manifestation (physical or virtual) and operation (manual or automatic). We exemplify the design space on a model embodying cardiovascular pathologies, represented by a mechanism where a liquid is pumped into a draining vessel, with complications illustrated through modifications to the model. The results of a mixed‐methods lab study with 28 participants show that both physical manifestation and manual operation have a strong positive impact on the audience's engagement. The study does not show a measurable knowledge increase with respect to cardiovascular pathologies using manually operated physical representations. However, subjectively, participants report a better understanding of the process—mainly through non‐visual cues like haptics, but also auditory cues. The study also indicates an increased task load when interacting with the process, which, however, seems to play a minor role for the participants. Overall, the study shows a clear potential of physicalization for the communication of complex dynamic processes, which only fully unfold if observers have to chance to interact with the process.